Freedom of Movement: Studying Women's Mobility in North India. (September 2021) - Mehta, Vidisha; Sai, Harish
'Freedom of movement' is an integral component of women's empowerment. However, according to the National Family Health Survey–4 (2015–2016), only 41 per cent of women in India enjoy complete mobility. This article examines women's mobility as a function of factors within the household—specifically a woman's relation to the household head—and its physical location, particularly whether it is located within a rural or an urban area. Using Bayesian inference techniques, we find that daughters-in-law are the least mobile, while spouses are the most. Additionally, we find that women are the most mobile when visiting the market and least mobile when visiting relatives. We also find that women from urban areas are more mobile than those in rural areas. The study goes on to enumerate the value of being able to move without any restrictions on employment. We establish that mobility is positively correlated with work. The article contributes to the limited research on urban women's mobility and agency and how it varies with household practices and spatial location.